Legal Efforts of Class I Bandar Lampung Penitentiary in Implementing Early Detection as an Effort to Prevent the Spread of Radicalism Ideology in Correctional Facilities - Kamal Fahmi Kurnia; M. Ryan Fajar Putra; Rian Guntama (CV. Publikasi Indonesia, 2023)
The problem in this study is: what are the inhibiting factors of Lembaga Pemasyarakatan Kelas I Bandar Lampung’s efforts in carrying out early detection as an effort to prevent the spread of radicalism in prisons? And how are the efforts of Lembaga Pemasyarakatan Kelas I Bandar Lampung in carrying out early detection as an effort to prevent the spread of radicalism inside? The research method is a normative and empirical juridical approach using secondary and primary data. Secondary data are obtained through literature studies, and primary data are obtained through field studies through observation and interviews. Then data analysis is carried out through qualitative legal analysis. The results of the study reveal factors inhibiting the efforts of Lembaga Pemasyarakatan Kelas I Bandar Lampung in carrying out early detection as an effort to prevent the spread of radicalism in residential block areas, including UU no 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. In practice, it has not been seen to have a real effect on preventing the spread of radicalism. Then the factor of prison officers finding it difficult to detect these radical ideas completely, the factor of facilities and infrastructure for handling radicalism crimes, is the lack of maximum supporting facilities, especially the improvement of facilities and infrastructure for fostering terrorism. The efforts of Lembaga Pemasyarakatan kelas I Bandar Lampung in carrying out early detection as an effort to prevent the spread of radicalism include forming a special unit, namely the Civil Service for terrorist prisoners, and forming a special guidance, namely the Pancasila Clinic, as a space for all prisoners without exception to learn national insight from the understanding of Pancasila, Bhinneka Tunggal Ika, UUD 1945, and NKRI. The suggestion that can be put forward is that Bandar Lampung Class I Prison should always improve facilities and infrastructure related to the special development of terrorism prisoners, where so far all prisoners have been equated in terms of coaching.